Electrospun hybrid nanofibers: Fabrication, characterization, and biomedical applications - Abadi, Banafshe; Goshtasbi, Nazanin; Bolourian, Saman; Tahsili, Jaleh; Adeli-Sardou, Mahboubeh; Forootanfar, Hamid (Frontiers in Bioengineering and Biotechnology, 2022)
Nanotechnology is one of the most promising technologies available today, holding tremendous potential for biomedical and healthcare applications. In this field, there is an increasing interest in the use of polymeric micro/nanofibers for the construction of biomedical structures. Due to its potential applications in various fields like pharmaceutics and biomedicine, the electrospinning process has gained considerable attention for producing nano-sized fibers. Electrospun nanofiber membranes have been used in drug delivery, controlled drug release, regenerative medicine, tissue engineering, biosensing, stent coating, implants, cosmetics, facial masks, and theranostics. Various natural and synthetic polymers have been successfully electrospun into ultrafine fibers. Although biopolymers demonstrate exciting properties such as good biocompatibility, non-toxicity, and biodegradability, they possess poor mechanical properties. Hybrid nanofibers from bio and synthetic nanofibers combine the characteristics of biopolymers with those of synthetic polymers, such as high mechanical strength and stability. In addition, a variety of functional agents, such as nanoparticles and biomolecules, can be incorporated into nanofibers to create multifunctional hybrid nanofibers. Due to the remarkable properties of hybrid nanofibers, the latest research on the unique properties of hybrid nanofibers is highlighted in this study. Moreover, various established hybrid nanofiber fabrication techniques, especially the electrospinning-based methods, as well as emerging strategies for the characterization of hybrid nanofibers, are summarized. Finally, the development and application of electrospun hybrid nanofibers in biomedical applications are discussed.